Effect of dietary patterns on cardiovascular risk factors in people with type 2 diabetes. A systematic review and network meta-analysis. (January 2023) - Bonekamp, N.E.; van Damme, I.; Geleijnse, J.M.; Winkels, R.M.; Visseren, F.L.J.; Morris, P.B.; Koopal, C.
Highlights: 73 RCTs on eight distinct dietary patterns were combined in a network meta -analysis. 6- and 12-month effects of dietary patterns on CVD risk factors were pooled. All dietary patterns outperformed usual diet in lowering body weight and HbA1c. Up to 16% relative CVD risk reduction can be achieved by a healthy dietary pattern. Abstract: Aims: To identify the most effective dietary pattern for improving cardiovascular risk factors in people with type 2 diabetes. Methods: PubMed, Embase, the Cochrane library, SCOPUS and Web of Science were systematically searched for randomized controlled trials comparing the effects of dietary patterns on body weight, blood pressure, HbA1c and lipids after 6 and 12 months. Treatment effects were synthesized using Bayesian network meta -analysis. Six-month changes in HbA1c, SBP and LDL-C were used to estimate relative risk reductions (RRR) for cardiovascular events. Results: Seventy-three RCTs on eight different dietary patterns were included. All reduced body weight and HbA1c after 6 months, with the largest effects from the low carbohydrate (body weight −4.8 kg, 95 %credibility interval (95 %CrI) −6.5;−3.2 kg) and Mediterranean diet (HbA1c −1.0 %, 95 %CrI -15;−0.4 % vs usual diet). There were no significant 6-month blood pressure or lipid effects. Dietary patterns had non-statistically significant 12-months effects. The Mediterranean diet resulted in the largest expected RRR for cardiovascular events: −16 % (95 %CI -31;3.0) vs usual diet. Conclusions: In patients with type 2 diabetes, all dietary patterns outperformed usual diet in improving body weight and HbA1c after 6 months and clinically relevant cardiovascular risk reduction could be achieved. There was insufficient evidence to select one optimal dietary pattern.